Willingness to communicate, communication apprehension and speaking anxiety among TESL undergraduates at the Faculty of Education / Muhammad Hanafi Md Zaini - Md Zaini, Muhammad Hanafi (2019)
It is necessary for educational institutions to develop the learners’ capacity in speaking since those who lack of speaking skills often face difficulties in convincing others in terms of asserting personal views and ideas. The inability of undergraduates to achieve speaking competence results in poor oral communication skills. Previous studies have acknowledged Willingness to Communicate, Communication Apprehension and speaking anxiety as the inhibitors in acquiring speaking competence. Therefore, this study investigates the relationship of Willingness to Communicate and Communication Apprehension on speaking anxiety among TESL undergraduates from the Faculty of Education at a public university in Selangor. The significance of MUET speaking score as the predictor of speaking anxiety along with the exploration of external affecting factors are included in this study. A mixed methods explanatory sequential design was employed in this study with the combination of questionnaire survey and semi-structured interview. In the quantitative phase, a total of 61 items were adopted in the questionnaire where 200 TESL undergraduates partook in the survey. The qualitative phase consisted of 14 semi-structured interview questions as 4 TESL undergraduates participated in the interview sessions. It was found that TESL undergraduates at the Faculty of Education had a high level of Willingness to Communicate and a moderate level of Communication Apprehension and speaking anxiety. Both Willingness to Communicate and Communication Apprehension had significant associations with speaking anxiety. However, it was discovered that MUET speaking score was not a prominent predictor for speaking anxiety. The qualitative findings revealed that several factors such as social status and speaking genres influence the undergraduates’ speaking anxiety. In brief, TESL undergraduates’ at the Faculty of Education had positive perspectives towards the use of English language in communication.